Aesthetic Characters of Flora and Fauna Painting Art Pengosekan on Visual Objects Wood Carving Craft Arts in Singakerta Village, Ubud - Ni Putu Laras, Purnamasari (Institut Seni Indonesia Denpasar, 2024)
Along with the heyday of Pengosekan flora and fauna painting in the 1990s, the aesthetic character of painting was attached to the art of wood crafts in Singakerta Village, Ubud. This aesthetic character can be seen from the visual style of creating flora and fauna objects as well as the finishing of wood carving crafts, which reveal images of typical Pengosekan flora and fauna paintings. This research specifically identifies the background and supporting factors for the visual language representation of Pengosekan flora and fauna painting objects in the art of wood carving that developed in Singakerta Village, Ubud. This research is qualitative research, using aesthetic theory and representation theory as analytical tools. The results of the research show that the aesthetic character of Pengosekan flora and fauna paintings is represented in wood carving craft products, in terms of theme, color, shape and visible lines. The representation that occurs is influenced by creativity in order to follow market trends that were developing at that time, as well as the economic motivation of the craftsmen to improve their welfare. The imagery of Pengosekan flora and fauna painting, which is attached to the art of wood carving, has indirectly helped the dynamic existence of this painting art. The representation of the art of painting in crafts is a dynamic that occurs in the development of the art of painting. The practice of indirect representation also shows something that is very important and positive in maintaining the existence of the art of painting itself, even though the visualization is slightly different because it is caused by several factors.